Venture capital funds: Flow-performance relationship and performance persistence - Phalippou, Ludovic (Journal of Banking & Finance, 2010)
This paper finds that venture capital funds that are expected to be backed by more skilled investors show no performance persistence but a significant flow-performance relationship. In contrast, funds that are expected to be backed by less skilled investors show performance predictability and have a non-significant flow-performance relationship. These results suggest that only skilled investors use all available information to adjust their capital allocation and, as a result, eliminate performance predictability as argued theoretically by Berk and Green (2004). Results also show that Kaplan and Schoar (2005) overstate the persistence in fund performance by not using an ex ante measure of the performance of earlier funds. Whether or not an ex ante measure is used, however, the persistence is largely due to unsophisticated investors. When investors are sophisticated, the performance of earlier funds, sequence and fund size do not help predict the performance of the focal fund.